(untitled) (Journal of Nematode Morphology and Systematics, 2010)
Ruehmaphelenchus asiaticus sp. n. isolated from packaging wood (Sterculariaceae) imported from the Republic of Korea to China is described. It is characterized by its body length of 737 (571-817) μm and 778 (710-888) μm of males and females, respectively; robust body (a = 29 and 25 of males and females, respectively); stylet 14.0 and 15.5 μm long for males and females, respectively; lateral field with three lines; mean value of vulva position 81%; long postuterine branch; female tail straight, tapering, and having a terminal spike up to 10 μm long in a central position (c= 27); spicules 18-20 μm long having a ventral flange, a pointed rostrum and the apex elongate and extending the line of the dorsal limb; male tail bluntly convex-conoid in shape and with a short claw-like hyaline process; three pairs of ventro-sublateral papillae (one pair preanal, two pairs postanal) and a single preanal papilla present; and bursa absent. The new species is the second known species of the genus. It can be distinguished from R. martinii by the round medium bulb, the different shape of the male tail (vs lacking the spike-like process) and the different shape of spicules. The characters used for definition of the genus are discussed. ITS-RFLP patterns of R. asiaticus sp. n. and sequencing results are shown.